2022
DOI: 10.3390/vaccines10111807
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bivalent mRNA Vaccines against SARS-CoV-2 Variants

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected billions of individuals and is the cause of the current global coronavirus disease 2019 (COVID-19) pandemic. We previously developed an mRNA vaccine (LVRNA009) based on the S protein of the Wuhan-Hu-1 strain; the phases I and II clinical trials showed that LVRNA009 has a promising safety and immunogenicity profile. In order to counteract the immune escape by SARS-CoV-2 variants of concern, a panel of mRNA vaccines was developed based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Brinkkemper’s study showed that co-display of wild-type and Beta spike proteins of SARS-CoV-2 on self-assembling nanoparticle platform broadens the neutralizing antibody responses ( Brinkkemper et al, 2022 ). Vaccines based on other components, such as S1 or NTD, are also suggested to enhance the broad spectrum of neutralizing antibodies ( Jiang et al, 2021 ; Li et al, 2022 ; Scheaffer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Brinkkemper’s study showed that co-display of wild-type and Beta spike proteins of SARS-CoV-2 on self-assembling nanoparticle platform broadens the neutralizing antibody responses ( Brinkkemper et al, 2022 ). Vaccines based on other components, such as S1 or NTD, are also suggested to enhance the broad spectrum of neutralizing antibodies ( Jiang et al, 2021 ; Li et al, 2022 ; Scheaffer et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several other COVID-19 mRNA vaccine candidates use LNPs to deliver various immunocargos, including PTX-COVID19-B (Modified SARS-CoV-2, NCT04765436), 548 ChulaCov19 (S-spike mRNA, NCT04566276), RQ3013 (modified S-spike mRNA, NCT05396573), LVRNA009 (modified mRNA, LVRNA009). 549 In addition to pure LNPs as a carrier for mRNA, the use of hybrid nanoparticles combining LNPs with inorganic materials has been investigated in clinical trials for COVID-19 mRNA vaccines. One such vaccine is HDT-301 (phase 1, NCT05132907, NCT04844268), which utilizes cationic squalene emulsion containing Fe 3 O 4 nanoparticles, along with the cationic lipid DOTAP and self-replicating replicon RNA (repRNA).…”
Section: Nanotechnology Adjuvants In Clinical Vaccines Against Infect...mentioning
confidence: 99%
“…Several other COVID-19 mRNA vaccine candidates use LNPs to deliver various immunocargos, including PTX-COVID19-B (Modified SARS-CoV-2, NCT04765436), 548 ChulaCov19 (S-spike mRNA, NCT04566276), RQ3013 (modified S-spike mRNA, NCT05396573), LVRNA009 (modified mRNA, LVRNA009). 549…”
Section: Clinical Development Of Nanotechnology Adjuvanted Vaccinesmentioning
confidence: 99%
“…The COVID-19 pandemic imposed new challenges to healthcare services, including requirement for novel immunoassays, immunotherapeutics based on neutralizing antibodies (nAbs), and new vaccinal platforms to assist the public health system and to reduce the increasing number of cases and deaths worldwide [ 4 , 5 , 6 , 7 , 8 ]. Since the onset of the COVID-19 pandemic, several variants of concern (VOCs) have emerged, including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), and the super-spread Omicron (B.1.1.529, BA.1, BA.2, BA.3, BA.4, and BA.5) [ 9 , 10 ]. The major concern about VOCs is related to their ability to increase transmission and/or virulence, and/or to escape current vaccine-induced immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may provide a simple and rapid platform for large-scale production of SARS-CoV-2 nAbs without the need for time-consuming procedures associated with viral isolation and/or production and purification of viral antigens [ 21 , 28 ]. Several DNA and mRNA vaccines expressing mainly the spike protein have been developed against SARS-CoV-2 and are being tested in clinical trials against COVID-19, which have confirmed the strong protective humoral and cellular immune responses in animal models [ 7 , 9 , 24 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%